Factors Influencing Malaysia Multi Level Marketing Distributors Acceptance of Digital Business Platform: A Moderating Effect of Gender - Lee, Sau Peng (2025)
This study investigates the factors influencing Malaysian Multilevel Marketing (MLM) distributors' acceptance of digital business platforms (BDPs), with a focus on the moderating effect of gender in the post-COVID-19 era. Grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT), a research model was developed to examine key determinants of behavioral intention (BI) to adopt BDPs. Both, offline and online survey methods were deployed to collect data. A total of 318 useful responses were returned by MLM distributors. Statistical analysis was performed using SPSS for descriptive statistics and PLS-SEM for inferential statistics. The findings revealed that performance expectancy, social influence, facilitating conditions, perceived trust, and perceived product attributes were statistically significant and positively influenced BI. Gender was found to significantly moderate the relationship between perceived product attributes and BI, while no significant moderating effects were observed for other variables. This study contributes to the academic literature by proposing and validating a novel research model for understanding BDP adoption in the MLM context. It offers valuable insights for industry stakeholders and policymakers, providing guidance on promoting digital platform adoption in the post-pandemic business environment.